Insight into 6-aminopenicillanic acid structure and study of the quantum mechanical calculations of the acid–base site on γ-Fe2O3@SiO2 core–shell nanocomposites and as efficient catalysts in multicomponent reactions. (23rd November 2020) - Saberi, Farveh; Ostovar, Somayeh; Behazin, Roya; Rezvani, Alireza; Ebrahimi, Ali; Shaterian, Hamid Reza
Abstract : Magnetic 6-APA/γ-Fe2 O3 @Sio2 nanocomposites have been developed by exploiting the potential of the acid–base bifunctional system to study the quantum mechanistic calculations. Abstract : Grafting 6-aminopenicillanic acid (6-APA) onto superparamagnetic γ-Fe2 O3 @SiO2 nanocomposites led to the production of 6-APA/γ-Fe2 O3 @SiO2 as a novel heterogeneous nanocatalyst. Protonation and deprotonation of 6-APA/γ-Fe2 O3 @SiO2 nanocomposites were investigated using quantum mechanical calculations. The behaviour of bifunctionality on this catalyst was examined and the results showed that it acts as an acid–base bifunctional system, and the reaction proceeds very well under mild and ambient conditions. The deprotonation of the COOH group is easier than the NH and NH2 groups with respect to the energy data and the results of the molecular electrostatic potential (MEP) analyses. In the presence of the nanocomposite, the protonation of the NH2 group is more favourable than the NH group. It was characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), vibrating sample magnetometery (VSM), thermo-gravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FT-IR). This reaction is not only kinetically stable but is also a spontaneous reaction and thermodynamically favored. The superparamagnetic nanocomposite was used in the preparation of 1, 4-dihydropyrano[2, 3- c ]pyrazole derivatives under a one-pot multicomponent reaction. The nanocomposite was recyclable for at least 10 cycles without any loss in the activity.